Pathomorphological features of the necrotic orbital wall lesions and orbital soft-tissue lesions in COVID-19-associated cavernous sinus thrombosis: a case report (Ukrainian Journal of Ophthalmology, 2025)
This paper describes a case of COVID-19-associated cavernous sinus thrombosis complicated by panophthalmitis, orbital cellulitis and necrotic purulent complications in other maxillofacial structures. In addition, we present the results of the pathomorphological study of orbital wall and orbital soft-tissue material excised during surgery. The pathomorphological findings in the orbital tissues included signs of a chronic inflammatory process with mostly lymphocyte infiltration, a proliferative component and development of mixed-type thrombi.
Keywords: COVID-19; cavernous sinus thrombosis; orbital cellulitis; pathomorphological study